Quantity of hemoperitoneum is associated with need for intervention in patients with stable blunt splenic injury. Issue 1 (9th February 2020) - Salottolo, Kristin; Madayag, Robert M; O'Brien, Michael; Yon, James; Tanner, Allen; Topham, Andrew; Lieser, Mark; Carrick, Matthew M; Mains, Charles W; Bar-Or, David
Abstract : Background: In patients with hemodynamically stable blunt splenic injury (BSI), there is no consensus on whether quantity of hemoperitoneum (HP) is a predictor for intervention with splenic artery embolization (SAE) or failing nonoperative management (fNOM). We sought to analyze whether the quantity of HP was associated with need for intervention. Methods: This retrospective cohort study included adult trauma patients with hemodynamically stable BSI admitted to six trauma centers between 2014 and 2016. Quantity of HP was defined as small (perisplenic blood or blood in Morrison's pouch), moderate (blood in one or both pericolic gutters), or large (additional finding of free blood in the pelvis). Multivariate logistic regression was performed to identify predictors of intervention with SAE or fNOM versus successful observation. Results: There were 360 patients: hemoperitoneum was noted in 214 (59%) patients, of which the quantity was small in 92 (43%), moderate in 76 (35.5%), and large in 46 (21.5%). Definitive management was as follows: 272 (76%) were observed and 88 (24%) had intervention (83 SAE, 5 fNOM). The rate of intervention was univariately associated with quantity of HP, even after stratification by American Association for the Surgery of Trauma (AAST) grade. After adjustment, larger quantities of HP significantly increased odds of intervention (p=0.01). Compared with no HP, the odds of intervention were significantly increased for moderate HP (OR=3.51 (1.49 to 8.26)) and large HP (OR=2.89 (1.03 to 8.06)), with similar odds for small HP (OR=1.21 (0.46 to 2.76)). Other independent predictors of intervention were higher AAST grade, older age, and presence of splenic vascular injury. Conclusion: Greater quantity of HP was associated with increased odds of intervention, with no difference in risk for moderate versus large HP. These findings suggest quantity of HP should be incorporated in the management algorithm of BSI as a consideration for angiography and/or embolization to maximize splenic preservation and reduce the risk of splenic rupture. Level of evidence: III, retrospective epidemiological study.